Bioelectrical impedance vector analysis in older adults: reference standards from a cross-sectional study - Campa, Francesco; Annunziata, Giuseppe; Barrea, Luigi; Sampieri, Alessandro; Ceolin, Chiara; De Rui, Marina; Sguaizer, Francesco; Petri, Cristian; Spataro, Fabrizio; Mascherini, Gabriele; Cremasco, Margherita Micheletti; Sergi, Giuseppe; et al. (Frontiers in Nutrition, 2025)
Background and AimsThe bioelectrical impedance vector analysis (BIVA) requires population-specific references to correctly classify individuals based on body composition properties. The aim of this study was: (i) to develop new references specific to the older adult population; (ii) to evaluate vector patterns based on age and appendicular lean soft mass (ALMS); (iii) to compare the new references with others already existing in the literature.MethodsThe present study included 835 older adults [472 women (mean age 73.9 ± 7.4 years, BMI 27.2 ± 5.4 kg/m2) and 363 men (mean age 73.1 ± 7.2 years, BMI 27.0 ± 4.4 kg/m2)]. Bioimpedance analysis was conducted using a phase-sensitive foot-to-hand technology at 50 kHz. Bioelectrical properties were analyzed among participants grouped by age categories and ALSM tertiles. New bivariate tolerance ellipses for resistance (R) and reactance (Xc), standardized by participants’ height (H), were compared with data from adult populations and the original BIVA references proposed by Piccoli in 1995 (ages 15–85).ResultsNew reference values for older adults were established. Significant differences (p < 0.001) in R/H and phase angle were observed when older adults were grouped by age categories, while R/H, Xc/H, and phase angle showed significant differences among ALSM/H2 tertiles. The mean bioelectrical vector for older adults differed from the references in the literature, showing a moderate magnitude relative to Piccoli’s original BIVA references (men: D2 = 0.6; women: D2 = 0.5) and a larger magnitude compared to the adult standards (men: D2 = 1.7; women: D2 = 1.8).ConclusionThis study provides BIVA references for older adults. Aging was associated with increased R/H and decreased phase angle, whereas older individuals with higher ALSM exhibited a greater phase angle and lower R/H, and Xc/H. The original BIVA references proposed in 1995 lack specificity and are no longer recommended for future use, as age-specific bioelectrical references are now available.